Pain in Dairy Cattle: A Narrative Review of the Need for Pain Control, Industry Practices and Stakeholder Expectations, and Opportunities - Steven Roche; Julia Saraceni; Laura Zehr; David Renaud (Animals)
Pain is an adverse experience causing distress and decreased production in dairy cattle. Pain, and its associated distress, is also undesirable from an animal welfare standpoint. Consumers consider animal welfare an important issue; therefore, ensuring proper pain management, and by extension good welfare, is important to maintain the social acceptability of dairy production. However, while some painful procedures and diseases can be avoided, some are inevitable. When this is the case, it is important to provide pain mitigation where possible. Various dairy quality assurance programs provide guidance on pain management practices for producers; however, guidelines differ across countries and jurisdictions. This narrative review covers common painful conditions and procedures, including disbudding and dehorning, castration, calving and dystocia, surgeries, disease conditions, and lameness. Further, this paper reviews evidence of the necessity and efficacy of pain management in these cases, current uptake of pain management, and quality assurance program standards for addressing pain in dairy cattle. Overall, there are clear advantages to providing pain mitigation for some conditions and procedures. For others, gaps still exist in understanding the best methods for pain control. Further attention should be paid to understanding and reducing the barriers to adoption of pain management strategies, as it is crucial to minimizing pain in animals and ensuring productive and sustainable dairy production.